2020
DOI: 10.1177/1049732320952740
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for PrEP-Related Interpersonal Communication Among Women Who Inject Drugs: A Qualitative Egocentric Network Study

Abstract: A qualitative egocentric social network approach was taken to explore motivations for pre-exposure prophylaxis (PrEP)-related communication between women who inject drugs and network members. Eligible participants were HIV-negative, 18 years or older, and participating in a PrEP demonstration project in Philadelphia, PA, USA. The study employed content analysis of in-depth interviews to identify themes related to contextual and relational factors impacting PrEP communication within networks. Participants ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Moreover, some of these trials showed that partner notification and support were important for PrEP adherence, as some of the women's partners encouraged and aided pill-taking behaviors (Mngadi et al, 2014;Montgomery et al, 2011Montgomery et al, , 2015. Results from several more recent studies corroborate earlier findings that some women wish to communicate with male partners about their oral PrEP use, although this literature remains underdeveloped (Felsher et al, 2021;Scorgie et al, 2021). For example, results from a qualitative study of women from Johannesburg and Mwanza revealed that, although many were eager to disclose their PrEP use to partners, some were more reluctant and others eschewed disclosure (Scorgie et al, 2021).…”
Section: How Has Prep Changed Sex For Cisgender Women?mentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, some of these trials showed that partner notification and support were important for PrEP adherence, as some of the women's partners encouraged and aided pill-taking behaviors (Mngadi et al, 2014;Montgomery et al, 2011Montgomery et al, , 2015. Results from several more recent studies corroborate earlier findings that some women wish to communicate with male partners about their oral PrEP use, although this literature remains underdeveloped (Felsher et al, 2021;Scorgie et al, 2021). For example, results from a qualitative study of women from Johannesburg and Mwanza revealed that, although many were eager to disclose their PrEP use to partners, some were more reluctant and others eschewed disclosure (Scorgie et al, 2021).…”
Section: How Has Prep Changed Sex For Cisgender Women?mentioning
confidence: 55%
“…Similarly, a study of women who inject drugs explored the motivating factors behind decisions to communicate with partners about PrEP use. Themes included communicating a benefit to their partners, increasing social connectedness, and meeting a perceived obligation to partners (Felsher et al, 2021).…”
Section: How Has Prep Changed Sex For Cisgender Women?mentioning
confidence: 99%
“…Another stigma reduction tool that would support PrEP care engagement could be packaging PrEP in important social infrastructures, such as SSPs. Research has identified SSPs as important for disseminating PrEP awareness [ 64 , 65 , 115 ]. Indeed, NYC participants reported learning about PrEP at their SSP and had greater PrEP knowledge because of conversations at the SSP.…”
Section: Discussionmentioning
confidence: 99%
“…This nding, along with our nding related to how SSPs in urban NYC relay information about "bad batches" that may contain fentanyl, highlight the important role that social networks of PWID in both urban and rural locations play in fentanyl-related information diffusion. Social networks of PWID have long been recognized as a source of information sharing, advice seeking, and support (61)(62)(63)(64)(65), and can contribute to uptake of pro-health behaviors and health and social services (62). For example, Sherman et al (2020) report that among participants in an overdose prevention and naloxone distribution program in Baltimore, MD, many were highly motivated to share information on overdose prevention and management, particularly the use of naloxone, to their peers and family (66).…”
Section: Discussionmentioning
confidence: 99%